INNOVATIVE TECHNOLOGIES IN THE RESTAURANT BUSINESS: IMPACT ON MANAGEMENT EFFICIENCY AND SERVICE QUALITY - TALAPA, STEFAN; POLIAK, MARIANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article considers innovative technologies as a new or improved systemic set of tools or methods of organizing activities that significantly improve production conditions or act as a commodity themselves. The main types of innovations and restaurant technologies are described. Technologies in the restaurant business (from special cooking methods to digital menu boards and loyalty software) offer great opportunities for investors, technologists and promising operators. The author analyzes current trends in the use of innovative technologies in the Ukrainian restaurant business. The author emphasizes the environmental friendliness of food and conscious consumption as innovative areas of development in the restaurant industry. Restaurant business establishments are trying to develop intensively: the use of technological innovations, the use of advanced equipment to optimize technological processes, expanding the range, increasing the production of semi-finished products of various degrees of readiness and culinary products with improved consumer characteristics. In the last decade, innovative food production technologies have been developed, such as low-temperature processing of meat, fish and seafood, vegetables and fruits; thermo-mixing and pacojetting; vacuum marinating, sublimation, emulsification, molding, texture control; aromatic cooking, distillation, herbojousing; freezing with liquid nitrogen. The Sous Vide technology (vacuuming products in a bag and cooking them in a water bath at a precisely defined temperature for a long period of time); food-pairing technique (combining different products that have a common flavor component) are also highlighted; molecular cuisine (a combination of products, the latest technology and molecular chemistry); CapKold technology (steaming a large volume of food and its rapid cooling in drums with ice water); fusion cooking (a harmonious combination of Western and Eastern gastronomy). Innovative technologies help to increase the number of visitors, expand the range of products, obtain high quality products and comply with all sanitary and hygienic standards, methods of ordering, and search for new original solutions for doing business in general.